2003
DOI: 10.1073/pnas.1833260100
|View full text |Cite
|
Sign up to set email alerts
|

GPI transamidase of Trypanosoma brucei has two previously uncharacterized (trypanosomatid transamidase 1 and 2) and three common subunits

Abstract: Glycosylphosphatidylinositol (GPI) anchor is a membrane attachment mechanism for cell surface proteins widely used in eukaryotes. GPIs are added to proteins posttranslationally by a complex enzyme, GPI transamidase. Previous studies have shown that human and Saccharomyces cerevisiae GPI transamidases are similar and consist of five homologous components: GAA1, GPI8, PIG-S, PIG-T, and PIG-U in humans and Gaa1p, Gpi8p, Gpi17p, Gpi16p, and Cdc91p in S. cerevisiae. We report that GPI transamidase of Trypanosoma br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
54
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 27 publications
1
54
0
Order By: Relevance
“…Mammalian/yeast GPI8/Gpi8p is a type I membrane protein with the majority of its sequence located in the ER lumen; GPI8 in many lower eukaryotes such as nematodes and trypanosomes is a soluble protein of the ER lumen, suggesting that the transmembrane domain is functionally dispensable (152,157). Consistent with this, a human GPI8 construct lacking the transmembrane domain can rescue GPI anchoring in GPI8 2 K562 cells (147).…”
Section: Transfer Of Gpis To Proteinmentioning
confidence: 80%
See 1 more Smart Citation
“…Mammalian/yeast GPI8/Gpi8p is a type I membrane protein with the majority of its sequence located in the ER lumen; GPI8 in many lower eukaryotes such as nematodes and trypanosomes is a soluble protein of the ER lumen, suggesting that the transmembrane domain is functionally dispensable (152,157). Consistent with this, a human GPI8 construct lacking the transmembrane domain can rescue GPI anchoring in GPI8 2 K562 cells (147).…”
Section: Transfer Of Gpis To Proteinmentioning
confidence: 80%
“…GPITs from Drosophila melanogaster, Caenorhabditis elegans, and Arabidopsis thaliana are similar to the mammalian/ yeast enzyme. In contrast, GPITs from trypanosomatids such as T. brucei share three subunits with mammalian/ yeast GPIT (homologs of GPI8, GAA1, and PIG-T termed TbGPI8, TbGAA1, and TbGPI16/PIG-T, respectively) but have two novel subunits (TTA1 and TTA2) in lieu of PIG-S and PIG-U (152,153). All five subunits are essential in both human and trypanosomatid-type GPIT, and all are needed for the nucleophilic attack on the v residue that produces the activated carbonyl intermediate to initiate transamidation (147,148,150).…”
Section: Transfer Of Gpis To Proteinmentioning
confidence: 99%
“…Gab1p is a very hydrophobic protein with many TMs [82,90]. While Gaa1p, Gpi8p and Gpi16p are common to all eukaryotic organisms, Gpi17p and Gab1p are absent from trypanosomatids, which latter possess two unrelated integral membrane proteins of similar membrane orientation, TTA1 and TTA2 instead [91]. The mammalian complex made of the five aforementioned subunits, when purified from digitonin extracts, is able to hold substrate proteins, which can be removed by washing with NP-40 [86].…”
Section: Addition Of Gpi Lipids To Proteinsmentioning
confidence: 99%
“…5,6 Trypanosomatids such as Trypanosoma brucei, share three subunits with mammalian/yeast GPIT (homologues of GPI8, GAA1 and PIG-T termed TbGPI8, TbGAA1 and bGPI16/PIGT, respectively) but have two novel subunits (TTA1 and TTA2) in lieu of PIG-S and PIG-U. 7 We recently found that phosphatidylinositol glycan class U (PIG-U), the human Gab1 orthologue, located on chromosomal band 20q11, is amplified and overexpressed in bladder cancer cell lines and primary tumors and causes malignant transformation in vitro and in vivo. 8 GPAA1 located on chromosomal region 8q24, and PIG-T located on chromosomal region 20q13.12, fall in the regions of copy number gain in breast cancer.…”
mentioning
confidence: 99%